(untitled) (Research, Society and Development, 2021)
Atemoya is a very perishable fruit that needs care during storage. Thus, this research aimed to evaluate the postharvest quality of ’Gefner’ atemoyas stored in modified atmosphere. The fruits were harvested at physiological maturity at the company Kabocla in Chapada do Apodi and transported to the IFCE Campus Limoeiro do Norte (CE), where they were selected and sanitized. Subsequently, the following treatments were applied: (T1) Control; (T2) part-time PVC; (T3) full-time PVC and (T4) 3% cassava starch. The fruits were stored in a cold chamber at 15 ± 4°C and relative humidity 85 ± 4%. A completely randomized design in a 4 x 6 factorial scheme was used, in which the first factor consisted of the types of coatings and the second of the storage times (0, 3, 6, 9, 12 and 15). Every three days, the following were analyzed: fresh mass loss, flesh firmness, external appearance, skin color, crack index, titratable acidity, pH, soluble solids, starch, total sugars, ratio and vitamin C. Expressive results were observed for weight loss of fruits coated with 3% cassava starch and control with 5.93 and 7.12%, respectively. During storage, all fruits showed loss of firmness and increased cracking index. The 3% cassava starch caused a loss of external quality and delayed changes in the color of the skin along with the other coatings, delaying the onset of cracks. The coatings provided a shelf life of 9 days.